PERKEMBANGAN PRAGMATIK DALAM PEMEROLEHAN BAHASA ANAK - Fitria Akhyar (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This study aims to describe theoritically related to the development of pragmatic category languages in children. The subjects studied were dominated by pre-school children (under 7 years). The method used in writing this paper is a literature study. Based on the literature that has been studied, it is found that: (1) in each context of dialogue there is a violation of the maxims with a certain frequency. Some responses from resource persons are straightforward and very informative or have adhered to the maxim of quantity, quality, relevance, and method; (2) the number of violations of maxims carried out by respondents can be seen as something natural and a natural process. (3) children preschool age still use positive politeness strategy to express their wishes.